Knowledge of type 2 diabetes mellitus and adherence to management guidelines: a cross-sectional study in Juba, South Sudan - Alexandre Ali M. Bili; Longying Zha (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2018)
Introduction: In South Sudan, inadequate education and the lack of efficient diabetes care centres compounded by high costs are common barriers for diabetes care. Objective: To assess the level of knowledge and adherence to guidelines for management of type 2 diabetes (T2D) and detected associations between knowledge scores and HbA1C levels. Method: A cross-sectional study among 176 participants aged from 20 to 79 years with T2D randomly selected in Malakia Diabetic Clinic, Juba from July to September 2017. Results: The proportions of "poor", "average", and "good" scores for knowledge were 58%, 18% and 24%, respectively. Fewer than half of the patients had had retinal check-ups (46.6%), HbA1c tests (44.3%), lipid measurements (37.5%), dental examinations (20.5%) and renal function reviews (10.2%) in the last year. Conclusion: There was poor knowledge and low adherence to diabetes management guidelines. This study highlights the significance of educational intervention and implementation of diabetes management guidelines in South Sudan.